Manufacture of Brick Titles From Local Raw Materials, N&NE Iraq - Merza, Tola A.; Mohyaldin, Ibrahim M. J. (Sulaimani Journal for Pure and Applied Sciences, 2005)
This study etablished to investigate the feasibility of using many types of local raw materials in Kurdistan for brick manufacture in this work fourteen types of clay were selected from differnet loculities in the region. The plasticity values of raw materials are indicate the direct relation to mineralogical composition . The samples which contain high percent of smectite and illite, have high to moderate plastiity, on the other hand the samples with high quartz content shwo low plasticity . The grain size analysis indicates the suitability of using raw materials form some localities in the studied area for manifacturing the perforate bricks , and others for roofing tiles and some others for thin wall product. Semi-dry method of forming eighty-four tiles under load 78kN/mm where adapted and fired at 850, 950 and 1050 C. for characteristics of the prepared tiles which are linear shrinkage, water absorption, bulk dentisty and compressive strenght are determined and found that some of these raw materials are suitable for manufacturing the solid and perforate bricks.
Keywords: Perforate bricks; roofing tiles; briquettes; and efflorescence